2020
DOI: 10.1038/s41598-020-73740-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive modelling of post-surgical recovery in individuals with cervical radiculopathy: a machine learning approach

Abstract: Prognostic models play an important role in the clinical management of cervical radiculopathy (CR). No study has compared the performance of modern machine learning techniques, against more traditional stepwise regression techniques, when developing prognostic models in individuals with CR. We analysed a prospective cohort dataset of 201 individuals with CR. Four modelling techniques (stepwise regression, least absolute shrinkage and selection operator [LASSO], boosting, and multivariate adaptive regression sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The RMSE score to predict NDI is similar to a model generated in people with cervical radiculopathy [ 82 ], with an RMSE of about 8.2% (NDI 0–100% scale). However, this comparison should be interpreted with caution due to the different populations.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The RMSE score to predict NDI is similar to a model generated in people with cervical radiculopathy [ 82 ], with an RMSE of about 8.2% (NDI 0–100% scale). However, this comparison should be interpreted with caution due to the different populations.…”
Section: Discussionmentioning
confidence: 64%
“…R statistical software was used to conduct this analysis. The functions, packages, and codes that were used to analyse this data have been described elsewhere [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…In [20] the ARMA models apply to likely linearly related year series. In [21] a step-wise regression is suggested as better over traditional LR or ARMA methods and this is also proven in this work empirically using specific ad-hoc ranges for LR orders and ARMA lags (delays). In [22] it is advocated that CC needs to be coupled with ML to reveal specific relationships across data.…”
Section: Discussionmentioning
confidence: 65%
“…The complexity between the predictors and outcome in previous studies [29,30] may be too low for ML to have a meaningful benefit over logistic regression. A previous study in cervical radiculopathy found nonlinear relationships between baseline selfreported predictors and 12 months clinical outcomes of neck and arm pain and disability [31]. The nonlinear relationship between baseline and outcomes may not be surprising given that previous studies reported different nonlinear rates of recovery in disability with different baseline neck disability scores in individuals with whiplash-associated disorders (WAD) [32].…”
Section: Discussionmentioning
confidence: 97%